Kawał a narracja - Wyrwas, Katarzyna (Stylistyka, 2021)
In this artice author describes joke as a narrative genre of speech. She analyses the texts of the Polish jokes to point the components of the narrative structure - Abstract, Orientation, Evaluation, Resolution and Coda. Some narrative jokes consist of only two components: Orientation and Evaluation, some of them has three components (full narrative structure): Orientation, Evaluation and Resolution. Narrative jokes can be also realized as enveloping structure. The components of this structure are Orientation and narrative sequence with few elements.